Code Switching and Code Mixing in the English Learning Process - Latifah, Ani (CV. Tripe Konsultan, 2024)
This research seeks to explore the function of language during the process of studying English within the classroom setting. The phenomenon of language in question is the occurrence of code switching and code mixing in classroom education. This kind of research is qualitative and descriptive. Data were collected from assertions that include code switching and code mixing during the English learning experience in the classroom. The intended conversation appears as a dialogue consisting of words, phrases, clauses, and sentences that showcase elements of code switching and code mixing, along with the functions of code switching and code mixing. The source of data was derived from dialogues occurring between students and teachers in the classroom. The method employed for gathering data involved recording techniques. The analytical method for data was applied to all speech indicating the use of code switching and code mixing in conversations between teachers and students within the classroom, specifically by condensing data, presenting data, and making inferences. According to the results of the research, different forms of Code Switching and Code Mixing occur in the process of learning English, which the researcher has detailed in the discussion.